Student’s Perception of Micro Teaching Course to Their Teaching Internship at The English Department of HKBP Nommensen University - Yolanda Erika Magdalena Pangaribuan; Kammer Tuahman Sipayung; Lastri Wahyuni Manurung; Adi Situmorang (Departement of Mathematics Education, 2023)
This study aims to find out student perceptions and benefits of the Micro Teaching Course for Teaching Internships at the English Department of HKBP Nommensen University. Researchers used a qualitative descriptive method. The population is seventh semester students of English education, amounting to 20 students. Data was collected through questionnaires and interviews. To collect data, the researcher gave 20 statement in the form of a questionnaire and then distributed them to 20 students and 7 questions through interviews with 10 students. From the results of the questionnaire the researchers concluded that students felt helped by their experiences in microteaching, as many as 20 participants 70% of whom agree and 29,75% strongly agree that microteaching had an effect on increasing their skills in teaching, From the results of the interviews, the researcher also concluded that students' perceptions of the microteaching course had an impact on their teaching practices as evidenced by the students' narrative presentations. Students think that with microteaching students can improve their skills in making and teaching based on lesson plans, skills in explaining material, time management and increasing self-confidence in teaching.